First record of Hololepta (Leionota) reichii (Marseul, 1853) (Coleoptera: Histeridae) in meliponaries of the state of Ceará (Brazil) and notes on the methods used to control this pest - Hiara M. Meneses; Epifânia E. de M. Rocha; Paloma Eleutério; Adriana A. Mota; Luiz W. Lima-Verde; Ana C. Dierings; Breno M. Freitas (Entomological Communications)
Meliponaries are an alternative for the preservation of stingless bee species, in addition to producing raw material for the pharmaceutical and cosmetic industry. The presence of invaders that can cause damage to the integrity of productive areas is something that is frequently reported. The same happens in meliponaries, where bees can have many natural enemies, whether vertebrates or invertebrates. Updating new records and management methods are crucial to avoid major losses in production. The aim of this work is to report the first occurrence of the clown beetles, Hololepta (Leionota) reichii (Marseul, 1853) (Insecta: Coleoptera: Histeridae) in meliponaries of the state of Ceará, Brazil, and provide notes on the methods used to control it. A total of 109 individuals (40 females; 69 males) were collected between February and July 2022, placed in alcohol 70%, and subsequently identified. Measures such as the removal of decaying organic materials from nearby the colonies, added to frequent inspection, internal and external cleaning of the hive boxes after infestations, in addition to the elimination of beetles found in the hives, had a positive effect in reducing the records of attacks.